Evaluation of Hematological Parameters in the Differentiation of Subarachnoid Hemorrhage and Other Headache Syndromes - Goktekin, Mehmet C.; Yilmaz, Mustafa (Clin Lab Publ, 2018)
Background: In this research, the aim was to compare hematological data for the differentiation of subarachnoid hemorrhage, migraine attack, and other headache syndromes during consultation in emergency service. Methods: In this research, which was designed as retrospective case control study, hematological parameters (WBC, HgB, HCT, PLT, lymphocyte and neutrophile counts and neutrophile/lymphocyte rates) of the patients consulting to emergency service with SAH and migraine and other consulting patients complaining mainly from headache and having normal cranial CT were analysed. Results: Sixty migraine attack patients (F/M:47/13), 57 SAH patients (F/M:30/27), and 53 patients except migraine having normal brain CT (F/M:36/17) who were consulted to emergency service with headache complaint were included in our research. WBC, Hct, HgB, MCV, PLT, MPV, LY, Neu counts, and NY/LY rates were found to differentiate between SAH and migraine. WBC, PLT, MPV, LY, and Neu rates were found to differentiate between SAH and HS patients. Only Hct, HgB, MCV, and NY/LY rates were found to differ meaningfully between SAH and migraine patients but these rates were not found to have meaningful difference between SAH and HS patients. In addition, an increase in WBC counts and NY/LY rates and decrease in MPV counts in ROC analysis were found to be more specific for SAH. Conclusions: WBC, HgB, HCT, PLT, lymphocyte and Neu counts, and NY/LY rates can indicate distinguishing SAH and migraine. WBC, HgB, HCT, PLT, lymphocyte and Neu counts can indicate to the clinician a differentiation of SAH and other headache syndromes.
Keywords: emergency service; headache; hematological parameters; migraine; subarachnoid hemorrhage